Phonetic phenomena in different languages - Maftuna Yusupova Baxtiyor qizi (Genius Journals, 2024)
The article deals with prevention and overcoming of typical mistakes, committing by polylingual students, studying English or in parallel with it, that should be based on comparative analysis of linguistic phenomena of contacting languages. In the first place, it allows to expose the source of interlingua transference, graduate the difficulties in studying new language, and, in the second place, sufficiently assist the students in comprehension of the phenomena of the studying language
Keywords: comparative analysis; interlingua transference; phoneme